Audiological profile of pre-operative and post-operative results in mucosal diseases of the ear: a comparative study - Mathri, Archana; Ahmed, Ruman; Malashetti, Santosh P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: The Objectives of the study were to study pre-operative audiological results in mucosal diseases of ear; to study post-operative audiological results in mucosal diseases of ear and to compare pre-operative and post-operative audiological results in mucosal diseases of ear. Methods: A prospective study was done on 60 patients presenting to out-patient department of Otorhinolaryngology and Head and Neck Surgery, S.Nijalingappa Medical College and H.S.K Hospital and Research Centre, Bagalkot from May 2018 to April 2020 with CSOM-mucosal disease. Audiological evaluation was done and compared using pure tone audiometry (Amplaid311TypeIEC645) before and after tympanoplasty with cortical mastoidectomy and mean air conduction (AC) threshold improvement and mean air-bone gap (AB gap) closure was analyzed. Results: Out of 60 patients, 27(45%) patients had medium sized central perforation. Mean pre-operative AC threshold was 44.5958±10.64639 dB HL which improved to 30.100±10.41056 dB HL at 1month and 21.8125±8.6928 dB HL at 3months post-operatively which was statistically significant with p<0.001*. Mean AB gap closure at 1-month was 10.175±6.01098 dB HL and at 3-months was 11.0416±6.3458 dB HL. Conclusions: AC threshold gain and AB gap closure at 1month and 3 months post-tympanoplasty with cortical mastoidectomy for CSOM-mucosal disease are significant. Hence surgery is main basic tool which results in improvement of audiological results in mucosal diseases of ear.